2013
DOI: 10.18433/j3kk6c
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of Academic Detailing to Optimize Medication Prescribing Behaviour of Family Physicians

Abstract: PURPOSE. To synthesize current knowledge about the effectiveness and the magnitude of the effect, of Academic Detailing (AD), as a stand-alone intervention, at modifying drug prescription behavior of Family Physicians (FPs) in primary care settings. METHODS. A search of MEDLINE, EMBASE, CENTRAL, and Web of Science databases of all English language articles between January 1983 and July 2010 was conducted. We hand-searched the bibliographies of articles retrieved from the electronic search to identify additiona… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
45
0
4

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(50 citation statements)
references
References 35 publications
1
45
0
4
Order By: Relevance
“…Twenty-eight reviews [20, 21, 29, 3256] ( n  = 509 studies) evaluated educational interventions. Evidence from moderate- to high-quality reviews demonstrated that education to improve knowledge and skills [3742, 48, 49, 5156], continuing medical education [20, 21, 29, 34, 43], and academic detailing [32] were found to be effective in professional development to increase knowledge, optimize prescriptions, screening rate, and improve patient outcomes [20, 29, 3236, 41, 44, 45, 50, 54].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Twenty-eight reviews [20, 21, 29, 3256] ( n  = 509 studies) evaluated educational interventions. Evidence from moderate- to high-quality reviews demonstrated that education to improve knowledge and skills [3742, 48, 49, 5156], continuing medical education [20, 21, 29, 34, 43], and academic detailing [32] were found to be effective in professional development to increase knowledge, optimize prescriptions, screening rate, and improve patient outcomes [20, 29, 3236, 41, 44, 45, 50, 54].…”
Section: Resultsmentioning
confidence: 99%
“…Evidence from moderate- to high-quality reviews demonstrated that education to improve knowledge and skills [3742, 48, 49, 5156], continuing medical education [20, 21, 29, 34, 43], and academic detailing [32] were found to be effective in professional development to increase knowledge, optimize prescriptions, screening rate, and improve patient outcomes [20, 29, 3236, 41, 44, 45, 50, 54]. Certain education interventions were evaluated as components of multifaceted education interventions, including interactive educational methods, reminder systems, audit and feedback, academic detailing, computer-based learning, lecture, as well as pamphlet in several reviews [29, 33, 36, 43, 44, 49]; which reported improvement in implementing guidelines into general practice [29], improved antibiotic prescribing [33], improved detection of cancer, dementia, and skin lesions [36, 44, 49].…”
Section: Resultsmentioning
confidence: 99%
“…Academic detailing is, in and of itself, an evidence-based, multi-component implementation strategy that includes needs assessments, education, and focused training and has contributed to successful implementation efforts across a number of domains. 24,[28][29][30][31] In VA, academic detailing is typically conducted by clinical pharmacists, who deliver face-to-face, 1-on-1 training. Our ndings support the notion that academic detailing is effective as a preimplementation, or "preparation" strategy, as we found that academic detailing measured prior to implementation was associated with the outcome.…”
Section: Discussionmentioning
confidence: 99%
“…Academic detailing is, in and of itself, an evidence-based, multi-component implementation strategy that includes needs assessments, education, and focused training and has contributed to successful implementation efforts across a number of domains. 21,24,25 In VA, academic detailing is typically conducted by clinical pharmacists, who deliver face-to-face, 1-on-1 training. Our findings support the notion that academic detailing may be most effective as a pre-implementation, or "preparation" strategy, as we found that academic detailing measured prior to implementation was associated with the outcome.…”
Section: Discussionmentioning
confidence: 99%